Risk of persistent high-grade squamous intraepithelial lesion after electrosurgical excisional treatment with positive margins: a meta-analysis - Oliveira, Caroline Alves de; Russomano, Fábio Bastos; Gomes Júnior, Saint Clair dos Santos; Corrêa, Flávia de Miranda (São Paulo Medical Journal, 2012)
CONTEXT AND OBJECTIVE: Even if precursor lesions of cervical cancer are properly treated, there is a risk of persistence or recurrence. The aim here was to quantify the risks of persistence of high-grade intraepithelial squamous lesions, one and two years after cervical electrosurgical excisional treatment with positive margins. DESIGN AND SETTING: Systematic review of the literature and meta-analysis at Instituto Fernandes Figueira. METHODS: This meta-analysis was on studies published between January 1989 and July 2009 that were identified in Medline, Scopus, Embase, Cochrane, SciELO, Lilacs, Adolec, Medcarib, Paho, Wholis, Popline, ISI Web of Science and Sigle. Articles were selected if they were cohort studies on electrosurgical excisional treatment of high-grade squamous intraepithelial lesions with a minimum follow-up of one year, a histopathological outcome of persistence of these lesions and a small risk of bias. RESULTS: The search identified 7,066 articles and another 21 in the reference lists of these papers. After applying the selection and exclusion criteria, only four articles were found to have extractable data. The risk of persistence of high-grade intraepithelial lesions after one year was 11.36 times greater (95% confidence interval, CI: 5.529-23.379, P < 0.0001) in patients with positive margins and after two years, was four times greater (95% CI: 0.996-16.164), although without statistical significance. CONCLUSION: This meta-analysis confirms the importance of positive margins as an indicator of incomplete treatment after the first year of follow-up and highlights the need for appropriately chosen electrosurgical techniques based on disease location and extent, with close surveillance of these patients.